Tensões entre currículo, educação física e desporto escolar : o significado educativo dos jogos escolares no contexto da escola - Casagrande, Carlos Roberto (2011)
The objective of this dissertation is to investigate the representation of the community school - students, teachers, parents, coordinators and directors – about how learning the students develop during the process of organization, preparation and participation in the School Games. Also wants to know how about they are incorporated in the training of school students. This research adopted a qualitative descriptive approach, in two schools community. These schools are located at Sinop City on Mato Grosso State. They participated in the Mato Grossense School Games (edition 2009). The research had as basis data collected through interviews and questionnaires. The benchmarks theorists, from this research, were based on Kunz (1994), Bracht (1986, 1992, 2003), Damiani and Escobar (2006), Barroso and Darido (2006), Nogueira and Catani (1998) and Taffarel and Stramann (2007). The set of results from this investigation, pointed to the possibility of learning when the students practice sport school. In this opportunity we tray to get another investigation: if there is some value in student participation on such games but not just as competition game based on numerical results, but as socialization experience and as a tool for academic research too. Therefore we had an opened vision about what they - coordinators, and teachers - think about improving students' learning as a whole. Most of educators don‘t like it questioned or shall be demonstrated indifferent to School Games. They can‘t see it as something that can bring learning to the student. This attitude, they say, is not arising by choice but we unknown the opportunities that present themselves to this rich experience as experienced by our students beyond teaching systematized.